Studies on the t-butyldimethylsilyl group as 2'-O-protection in oligoribonucleotide synthesis via the H-phosphonate approach. - Stawinski, J (1988)
Two model compounds, 1 and 2, have been studied to test the stability of the t-butyldimethylsilyl (t-BDMSi) group towards conditions used during chemical synthesis of RNA fragments by the H-phosphonate approach. When 1 was treated with anhydrous acid for 16 h both the H-phosphonate diester and the t-BDMSi group remained intact. Removal of the t-BDMSi group from 2 with 1.0 M tetrabutylammonium fluoride (TBAF .3H2O) in THF was complete within 4 h and neither concomitant cleavage nor migration of the phosphodiester linkage could be detected even after 24 h. The dimer 2 was not completely stable towards concentrated aqueous ammonia and both loss of the t-BDMSi group and concomitant cleavage of the phosphodiester linkage occurred upon prolonged treatment. These reactions were substantialy suppressed in ethanol containing ammonia solutions, however to alleviate this problem during oligoribonucleotide synthesis, more labile protecting groups for heterocyclic bases would be desired. In conclusion, these studies indicate that 2'-O-t-BDMSi can be considered as a convenient and safe protecting group, which should secure synthesis of oligoribonucleotides with exclusively 3'-5' internucleotidic linkages.